Development and Validation of A Self-Confidence Measurement Instrument In Mathematics Learning Using The Rasch Model - Dewanti, Sintha Sih; Ashabulabib, Adib; Dewi, Indriana Puspita; Islamiyah, Aris Mislikhatun (Universitas Wiralodra, 2025)
Self-confidence is a critical factor in mathematics learning, influencing students' engagement and performance. However, studies show that Indonesian students often lack confidence in mathematics subject, hindering their academic potential. Accurate instruments are needed to measure and address this issue effectively. This tudy aims to develop a self-confidence measurement instrument for mathematics learning among secondary school students. The instrument comprises 25 statements categorized into four main aspects. The research employs a descriptive quantitative method with the Rasch Model approach and utilizes exploratory and confirmatory factor analysis. The sample consists of 122 randomly selected tenth-grade students in Yogyakarta. The results indicate that the developed instrument has high validity, with an Aiken's V coefficient of 0.99, and very high reliability, evidenced by a Cronbach's Alpha coefficient of 0.845 with a total of 18 items used. Factor analysis shows that the items in the self-confidence questionnaire meet the unidimensionality requirement, although some items need correction to enhance measurement accuracy for one self-confidence indicator. Overall, this instrument provides a valid and reliable tool for measuring students' self-confidence in mathematics learning, potentially contributing to the enhancement of students' confidence in this subject. So that, 18 statements are more efficient to use, without reducing the scope of the self-confident aspect being measured. The results allow the use of instruments for various levels of education and support the implementation of more personalized learning strategies.